2018
DOI: 10.1089/neu.2015.3993
|View full text |Cite
|
Sign up to set email alerts
|

Activating Transcription Factor-6α Deletion Modulates the Endoplasmic Reticulum Stress Response after Spinal Cord Injury but Does Not Affect Locomotor Recovery

Abstract: The endoplasmic reticulum stress response (ERSR) is activated in a variety of neurodegenerative diseases and/or traumatic injuries. Subsequent restoration of ER homeostasis may contribute to improvement in the functional outcome of these diseases. We recently demonstrated improvements in hindlimb locomotion after thoracic spinal cord injury (SCI) and implicated oligodendrocyte survival as a potential mechanism using genetic and pharmacological inhibition of the protein kinase ribonucleic acid-like ER kinase- C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…PERK, ATF6, and IRE-1, all three arms of the ER stress response signaling pathway, are all known to be activated after SCI 31 . It also has been found that ablation of ATF6 does not affect locomotor recovery after spinal cord injury; and attenuation of PERK is a viable therapeutic target to improve functional recovery after SCI 32 , 33 . The function of IRE-1 inhibition in spinal cord injury has not been determined.…”
Section: Resultsmentioning
confidence: 99%
“…PERK, ATF6, and IRE-1, all three arms of the ER stress response signaling pathway, are all known to be activated after SCI 31 . It also has been found that ablation of ATF6 does not affect locomotor recovery after spinal cord injury; and attenuation of PERK is a viable therapeutic target to improve functional recovery after SCI 32 , 33 . The function of IRE-1 inhibition in spinal cord injury has not been determined.…”
Section: Resultsmentioning
confidence: 99%
“…Models of mechanical damage, such as occurs in NIHL, have implicated the UPR in neurons. In a study of crushed optic nerves, treatment of mice with ISRIB reduced axonal degeneration 17 , and UPR modulation improved recovery after spinal cord injury in mice 18 . Our work in genetic and noise-induced mouse models has similarly demonstrated a role for ER Ca 2+ dysregulation as a link between acoustic overstimulation and UPR activation 4 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the activation of ATF6 branch of the UPR was also reported to improve the outcomes after cerebral ischemia( Yu et al, 2018 ). On the contrary, it has been demonstrated in a rat model of spinal cord injury, that knockout of ATF6 could protect against ER stress and promote oligodendrocyte precursor cell survival ( Saraswat et al, 2018 ). Actually, the activation of ATF6 branch of UPR has dual roles in the regulation of cell survival.…”
Section: Discussionmentioning
confidence: 99%